Closing Letter of RILEM TC 282-CCL: Calcined Clays as Supplementary Cementitious Materials - José Fernando Martirena Hernández; Manu Santhanam (RILEM Technical Letters)
With over 8% of global carbon emissions worldwide, the cement industry is challenged to lower its carbon footprint. Replacement of clinker in cementitious systems becomes crucial. Sound research proved that kaolinitic clays with as low as 40% kaolinite can have a high reactivity as SCM. Further research studies found a synergy between the aluminates in calcined clays and the carbonates in limestone that led to the proposal of a ternary binder called Limestone Calcined Clay Cement, LC3, consisting of 50% Portland Cement, 30% calcined clay and 15% limestone. This paper presents the efforts of a group of members from 41 universities and 17 industrial partners through the RILEM Technical Committee 282 – CCL: Calcined Clays as Supplementary Cementitious Materials. The work was oriented to fill existing information gaps on characteristics of clay minerals, the process of clay calcination, hydration of cementitious systems containing calcined clay and limestone, fresh and hardened properties of concrete, standardization, and durability of concrete produced with binders containing calcined clay and limestone. The TC 282-CCL has published 10 whitepapers, with a strong contribution to a better knowledge and understanding of the role of calcined clay in cement and concrete.